Learn And Apply Blockchain And Ai Technology In Buying And Selling Items With Virtual Currency - Doan, Nguyen Hung (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Software Engineering; 2020 - 2025